2019
DOI: 10.5205/1981-8963-v13i3a238069p632-639-2019
|View full text |Cite
|
Sign up to set email alerts
|

Intervenções de enfermagem para pacientes com dor aguda

Abstract: RESUMO:Objetivo: identificar as intervenções de Enfermagem realizadas para pacientes com dor aguda. Método: trata-se de um estudo qualitativo, exploratório e descritivo, realizado em uma unidade de pronto atendimento de um hospital filantrópico. Adotou-se o procedimento de triangulação de técnicas. Desenvolveu-se o estudo em três etapas: análise documental; mapeamento cruzado à Nursing Interventions Classification (NIC)13 para a dor e validação das intervenções de Enfermagem por meio de um grupo focal. Resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
3
1
5
Order By: Relevance
“…As for the presence of the registry of pain in the records, one study evaluating hospitalized patients in a secondary hospital observed lack of pain registry in 53,4% of assessed medical records 7 , a slightly inferior number to the one observed in the present study, which found flaws in the pain record of 61,9% of patients. The flaw in the records of pain supports the findings in the literature that point to a lack of professional knowledge in regard to the evaluation and control of pain 8,9,15 .…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…As for the presence of the registry of pain in the records, one study evaluating hospitalized patients in a secondary hospital observed lack of pain registry in 53,4% of assessed medical records 7 , a slightly inferior number to the one observed in the present study, which found flaws in the pain record of 61,9% of patients. The flaw in the records of pain supports the findings in the literature that point to a lack of professional knowledge in regard to the evaluation and control of pain 8,9,15 .…”
Section: Discussioncontrasting
confidence: 88%
“…Identifying the complaint of pain and the consequences of acute pain for the patient's recovery should be a nurse's concern. Knowledge gaps on pain assessment and management and the lack of systematization of this care contributes to underreporting and inadequate treatment, despite the various assessment and management tools available [5][6][7][8][9][10] . A literature review that analyzed studies on the recording of post surgery pain in the hospital context showed that the quality of nurse records about pain are insufficient, affect the clinic decision making and undermine the continuity of care 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The institutional protocol of analgesia, which included the administration of medication at regular intervals, certainly contributed for this diagnosis not to prevail. Among the interventions, the administration of analgesics (2210) and Pain control (1400) through pharmacological and non-pharmacological methods were highlighted, as well as monitoring through verbal and non-verbal indicators ( 15 , 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, related factors included pain and food intolerance, which are associated with an infant’s oral impairment and the invasive procedure ( 14 ) . The main interventions were focused on Pain Control (1400), Oral Health Restoration (1730), Nutrition Control (1100) and Calming Techniques (5880), besides providing family support and promoting adequate sleep ( 15 , 23 , 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Com base nos artigos achados, como descrito na metodologia, percebe-se a importância da enfermagem na prevenção do suicídio e na promoção de saúde mental da população, como descrito na tabela 1. No estudo conduzido por Caciano et al (2019), os resultados revelaram uma série de intervenções de Enfermagem essenciais para pacientes neurocríticos em UTIs. Algumas das intervenções mais relevantes incluíram o uso da Escala de Coma de Glasgow, que auxilia na avaliação do nível de consciência do paciente, e a Escala de Agitação e Sedação Richmond, para monitorar o grau de sedação necessário.…”
Section: Enfermagem Na Assistência Aos Familiaresunclassified